Internet Addiction Among University Students: Psychometric Properties of Three Factor Model Internet Addiction Test - Prashanth, Talwar Yadar; Fitri Suraya, Mohamad; Mohamed Sharif, Bin Mustaffa; Mohd Kamal, Bin Othman; Oon, Yin Bee; Chai, Chiun Hian (OJHAS Publisher, 2019)
Incursion of the Internet into daily life has become problematic for an increasing number of people, particularly for individuals with the affliction which is often referred as Internet Addiction (IA). Burgeoning global research has demonstrated the perceptible adverse consequences of IA, especially among students. Of the available scales that assess IA, thus far the most extensively used has been the Internet Addiction Test (IAT). However, several prior psychometric analyses have portrayed ambiguous factor structures. The main aim of the present study was to provide data on its factorial structure and ascertain its reliability in a sample comprising 307 university students. Convenience sampling technique was employed in this cross-sectional study wherein a bilingual version of IAT was administered to participants. Findings revealed that nearly 32% students could be considered as moderately addicted, and 3% as severely addicted. Examination of the latent structure of the IAT scale using both exploratory and confirmatory factor analysis revealed a 3-factor solution (lack of control, excessive use and compulsion) which explained 48% total variance. Also, low factor loadings on Item 8 prompted its exclusion. Subsequent multi-group CFA showed that the scores for this model were invariant in terms of gender. The resulting 19-item IAT with a three-factor structure appears to be a valid and reliable instrument for measuring IA. Though initial indications of construct validity were promising, additional research may still be required to elucidate the stability of factor solutions in a variety of settings and demographic backgrounds in Malaysia.